The Effect of Job Demand and Burnout on Employee Performance at PT. Bank Tabungan Negara (Persero) Tbk. Medan Branch Office - Pratiwi, Okky; Mardhiyah, Ainun (PT FORMOSA CENDEKIA GLOBAL, 2024)
Performance is the result of work achievement based on responsibility in achieving the goals of a company or organization which can be measured based on quality and quantity. The research method used in this research is quantitative research with an associative approach. Sampling was carried out using probability sampling techniques with a simple random sampling model, using the Slovin formula, totaling 61 respondents. The results of the research conducted show that the work demand variable does not have a significant effect on employee performance. Meanwhile, it is known that the burnout variable has a significant effect on employee performance. The coefficient of determination test shows that there is a close relationship between job demand and burnout on employee performance with an R value of 0.706. Through the Adjusted R Square value, it is also known that the job demand and burnout variables contribute 48.1% to the employee performance variable while the remaining 51.9% is influenced by other variables not discussed in this research.